2014
DOI: 10.1371/journal.pone.0112676
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inflammatory Cytokine Levels Correlate with Hand-Foot-Mouth Disease Severity: A Nested Serial Case-Control Study

Abstract: BackgroundHand-food-mouth disease (HFMD) cases can be fatal. These cases develop rapidly, and it is important to predict the severity of HFMD from mild to fatal and to identify risk factors for mild HFMD. The objective of this study was to correlate the levels of serum inflammatory cytokines with HFMD severity.MethodsThis study was designed as a nested serial case-control study. The data collected included general information, clinical symptoms and signs, laboratory findings and serum cytokine levels.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 30 publications
(33 reference statements)
2
42
0
Order By: Relevance
“…TNF-α involves the occurrence and development of many diseases, which can promote the production of various inflammatory factors by T cells to promote the occurrence of inflammatory response. The serum levels of TNF-α in severe EV71-infected patients were significantly higher than those in mild patients [10][11][12] (shown as Table 1), which indicated that TNF-α may be involved in disease severity. High levels of TNF-α were detected in severe patients with complications (including brainstem encephalitis, neurogenic pulmonary edema, and sepsis) at disease onset, and then decreased with disease progression [10].…”
Section: Tnf-αmentioning
confidence: 93%
See 3 more Smart Citations
“…TNF-α involves the occurrence and development of many diseases, which can promote the production of various inflammatory factors by T cells to promote the occurrence of inflammatory response. The serum levels of TNF-α in severe EV71-infected patients were significantly higher than those in mild patients [10][11][12] (shown as Table 1), which indicated that TNF-α may be involved in disease severity. High levels of TNF-α were detected in severe patients with complications (including brainstem encephalitis, neurogenic pulmonary edema, and sepsis) at disease onset, and then decreased with disease progression [10].…”
Section: Tnf-αmentioning
confidence: 93%
“…The serum levels of TNF-α in severe EV71-infected patients were significantly higher than those in mild patients [10][11][12] (shown as Table 1), which indicated that TNF-α may be involved in disease severity. High levels of TNF-α were detected in severe patients with complications (including brainstem encephalitis, neurogenic pulmonary edema, and sepsis) at disease onset, and then decreased with disease progression [10]. The critical HFMD group (frequent convulsions, coma, brain hernia, pulmonary rales, or circulatory insufficiency) also had higher levels of TNF-α than the severe group (acute flaccid paralysis or convulsions) and mild group [11].…”
Section: Tnf-αmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in our previous study, the highest levels of some inflammatory cytokines occurred at 3 dpi in HFMD cases. In terms of above results, RAS activation may induce large amounts of pro-inflammatory cytokines [23]. Numerous studies on the pathogenesis of other viral diseases have also shown that pathogens can affect the stability of the RAS [24][25][26][27].…”
Section: Discussionmentioning
confidence: 93%